Development of Electronic Fuel Injection System for Single Cylinder Small Engine - Mohamad Farid bin Esa, Mohamad Farid (Universiti Teknologi Petronas, 2009)
The project focuses on the development of an electronic fuel injection system for a single cylinder small engine. The engine currently used a carburettor fuelling system which is less efficient in fuelling control thus resulting in high fuel consumption, lower engine performances that contribute to poor emission released to the environment. The main idea of the project is to develop an electronic fuel injection control system on the current single cylinder engine to improve the engine operating region of efficiency and hence produces a better engine performance. In addition, the electronic fuel injection system should be capable of producing a better fuel controls thus resulting improved emission.